Fermented red ginseng and ginsenoside Rd alleviate ovalbumin-induced allergic rhinitis in mice by suppressing IgE, interleukin-4, and interleukin-5 expression - Hye In Kim; Jeon-Kyung Kim; Jae-Young Kim; Myung Joo Han; Dong-Hyun Kim (Journal of Ginseng Research, 2019)
Background: To increase the pharmacological effects of red ginseng (RG, the steamed root of Panax ginseng Meyer), RG products modified by heat process or fermentation have been developed. However, the antiallergic effects of RG and modified/fermented RG have not been simultaneously examined. Therefore, we examined the allergic rhinitis (AR)-inhibitory effects of water-extracted RG (wRG), 50% ethanol-extracted RG (eRG), and bifidobacteria-fermented eRG (fRG) in vivo. Methods: RBL-2H3 cells were stimulated with phorbol 12-myristate-13-acetate/A23187. Mice with AR were prepared by treatment with ovalbumin. Allergic markers IgE, tumor necrosis factor-α, interleukin (IL)-4, and IL-5 were assayed in the blood, bronchoalveolar lavage fluid, nasal mucosa, and colon using enzyme-linked immunosorbent assay. Mast cells, eosinophils, and Th2 cell populations were assayed using a flow cytometer. Results: RG products potently inhibited IL-4 expression in phorbol 12-myristate-13-acetate/A23187-stimulated RBL-2H3 cells. Of tested RG products, fRG most potently inhibited IL-4 expression. RG products also alleviated ovalbumin-induced AR in mice. Of these, fRG most potently reduced nasal allergy symptoms and blood IgE levels. fRG treatment also reduced IL-4 and IL-5 levels in bronchoalveolar lavage fluid, nasal mucosa, and reduced mast cells, eosinophils, and Th2 cell populations. Furthermore, treatment with fRG reduced IL-4, IL-5, and IL-13 levels in the colon and restored ovalbumin-suppressed Bacteroidetes and Actinobacteria populations and ovalbumin-induced Firmicutes population in gut microbiota. Treatment with ginsenoside Rd significantly alleviated ovalbumin-induced AR in mice. Conclusion: fRG and ginsenoside Rd may alleviate AR by suppressing IgE, IL-4, IL-5, and IL-13 expression and restoring the composition of gut microbiota. Keywords: Allergic rhinitis, Fermentation, Ginsenoside Rd, Gut microbiota, Red ginseng